Increase Noise Hazard on Incident of Occupational Diseases in Agroindustrial Area - Kurniyawan, Enggal Hadi; Isyroq, Haidar Fadhilatin; Rifa’i, Achmad; Rusmawati, Adinda Athalia; Ramadhan, Ibadillah Hilmy Dzulfiqar; Kurniawan, Dicky Endrian; Nur, Kholid Rosyidi Muhammad (Rajaki of Tulip Medika Publisher, 2023)
Background: The sound generated by a tractor engine is one of the causes of ear disorders. This is usually experienced by people who live in agro-industrial areas, especially those who work as farm laborers, especially when planting and harvesting. Most people spend their free time in the fields, so they indirectly listen to the sound produced by the tool. Purpose: The literature review study aims to discover the increase of noise hazards on incidents of occupational diseases in agro-industrial areas. Methods: The method used in the preparation of this Literature Review was obtained from 3 database sources, namely Google Scholar, ScienceDirect, and Pubmed, which was published from 2018 to 2021 using Indonesian keywords, namely